The Mediation Role of School Alienation Between Perceptions of the School Atmosphere and School Refusal in Italian Students - Luana Sorrenti; Angelo Fumia; Concettina Caparello; Carmelo Francesco Meduri; Pina Filippello (Education Sciences, 2025)
School Atmosphere (SAt) plays a crucial role in shaping students’ academic success and emotional well-being. When students perceive a negative SAt, this can lead to feelings of School Alienation (SAl), which are associated with School Refusal (SR). Despite previous research on school climate and SR, the dimension of SAt, which encompasses the intangible aspects (quality of relationships and justice perceptions) of the school environment, remains a topic of limited examination. Furthermore, the mediating role of SAl between these variables remains underexplored. This study aims to examine how SAl (learning alienation, teacher alienation, and classmate alienation) mediates the relationship between students’ perceptions of SAt (educational climate, student–teacher relations, student relations, sense of belonging, and interpersonal justice) and SR (anxious anticipation, difficult transition, interpersonal discomfort, and school avoidance). Data were collected from 528 Italian high school students (aged 14–20), and using structural equation modeling (SEM), the direct and indirect relationships between SAt variables, dimensions of SAl, and SR were assessed. The results indicated that negative perceptions of interpersonal justice and sense of belonging were strongly associated with higher levels of learning and teacher alienation, which are linked to SR, particularly anxious anticipation and difficult transition. The results emphasize the importance of promoting fairness, belonging, and supportive student–teacher relationships to mitigate alienation and improve student success. This study highlights the need for comprehensive strategies to foster positive school environments and prevent disengagement and absenteeism, ultimately promoting academic success and student well-being.